การประเมินโครงการงานสวนพฤกษศาสตร์โรงเรียนโรงเรียนเตรียมอุดมศึกษาพัฒนาการ นนทบุรี - Tiengkool, Bhirom; Chaiso, Porntip; Pitiporntapin, Sasithep (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2016)
The Evaluation of School Botanical Garden Project in Triamudomsuksapattanakarn Nonthaburi School Bhirom Tiengkool, Porntip Chaiso, Sasithep Pitiporntapin รับบทความ: 15 กรกฎาคม 2559; ยอมรับตีพิมพ์: 29 กันยายน 2559 บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อประเมินโครงการงานสวนพฤกษศาสตร์โรงเรียน โรงเรียนเตรียมอุดมศึกษาพัฒนาการ นนทบุรี โดยใช้วิธีการเชิงระบบ ซึ่งประเมินเกี่ยวกับความเหมาะสมของปัจจัยนำเข้า ความเหมาะสมของกระบวนการดำเนินงาน และผลที่เกิดจากการดำเนินงานตามโครงการฯ ประจำปีการศึกษา 2557 กลุ่มที่ศึกษา คือ ผู้บริหารโรงเรียนจำนวน 4 คน ครูจำนวน 115 คน และนักเรียนจำนวน 602 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบสัมภาษณ์ผู้บริหาร แบบสอบถามครูและนักเรียน วิเคราะห์ข้อมูลเชิงปริมาณ โดยการหาค่าความถี่ ร้อยละ และการวิเคราะห์ข้อมูลเชิงคุณขภาพโดยการวิเคราะห์เนื้อหา แปลผลการประเมิน โดยการเปรียบเทียบข้อมูลกับเกณฑ์ที่กำหนดไว้ ผลการวิจัย พบว่า ปัจจัยนำเข้าของโครงการมีความพร้อมด้านอาคารสถานที่ มีความพร้อมของครูที่ดำเนินโครงการ และมีความพร้อมของงบประมาณอยู่ในระดับดี ส่วนที่ต้องปรับปรุงคือ ความพร้อมของวัสดุ–อุปกรณ์ที่ใช้ในการดำเนินงาน และการให้สนับสนุนจากผู้บริหารอย่างต่อเนื่องในการติดตามการดำเนินงานตามโครงการ ส่วนความเหมาะสมของกระบวนการดำเนินงานตามโครงการฯ ซึ่งมีการประ-เมินใน 4 กิจกรรม ผู้วิจัยพบว่า ทุกกิจกรรมมีการดำเนินงานเหมาะสมอยู่ในเกณฑ์ดี ได้แก่ 1) กิจกรรม 5 องค์ประกอบงานสวนพฤกษศาสตร์โรงเรียน 2) การอบรมครูเรื่อง การนำงานสวนพฤกษศาสตร์โรงเรียนสู่การจัดการเรียนรู้ 3) กิจกรรมค่ายพฤกษศาสตร์ และ 4) กิจกรรมการนำงานสวนพฤกษศาสตร์สู่การจัดการเรียนรู้ ส่วนผลที่เกิดจากการดำเนินงานตามโครงการฯ มีผลการประเมินในระดับดีมาก ทั้งผลที่เกิดขึ้นกับโรงเรียน นักเรียน และครูในภาพรวม นอกจากนี้ยังพบว่า ผู้บริหาร ครู และนักเรียนพึงพอใจต่อการดำเนินงานตามโครงการงานสวนพฤกษศาสตร์โรงเรียนในระดับดี และเพื่อให้โครงการดำเนินงานได้อย่างมีประสิทธิภาพมากขึ้น ผู้บริหารควรมีนโยบายและแผนการดำเนินงานอย่างชัดเจน ควรเข้ามามีส่วนร่วมในกิจกรรมต่าง ๆ ของโครงการ ควรมีการติดตามผลการดำเนินงานอย่างต่อเนื่อง และสนับสนุนให้มีการอบรมพัฒนาครูรุ่นใหม่เกี่ยวกับการดำเนินงานตามโครงการงานสวนพฤกษศาสตร์โรงเรียน คำสำคัญ: การประเมินโครงการ การประเมินเชิงระบบ สวนพฤกษศาสตร์โรงเรียน Abstract The objective of this study was to evaluate the botanical garden project at Triamudomsuksapattanakarn Nonthaburi School using the systematic approach. The evaluation was about the appropriate of input factors, operations, and output factors of this project in the academic year 2014. The research participants were divided into 3 groups: 4 school administrators, 115 teachers and 602 students. The research instruments of this study were the interview schedule and the questionnaire. The researcher analyzed quantitative data by calculating frequencies and percentages, and qualitative data by content analyses. The data were interpreted by comparing with the defined criteria. The findings were indicated that the project has appropriateness in location, the teachers responsible for operating the project and the budgets were the driving factors that make this project well organized at good level. However, the materials used in the project, and the continuing supports from the school administrators for tracking of project operation should be improved. For the project operations in 4 activities, the researcher found that all activities were at good level including 1) 5 components of the school botanical garden activities; 2) teacher workshops about linking the school botanical garden to teaching and learning; 3) the school botanical camp; and 4) the activities for teachers’ linking the school botanical garden to their teaching and learning. The output of the school botanical garden project effect on the school, teachers and students were at excellent level. In addition, the researcher found that the school administrators, teachers and students had satisfactions of the project at good level. For more effective project operations, the school administrators had to clear policy and plan about the project, should participate more in all activities, follow-up the project continuously and should support new teachers for training in the project operation. Keywords: Project evaluation, Systematic evaluation, School botanical garden